TACKLING NEGLECTED TROPICAL DISEASES THROUGH PARTNERSHIP - PROFESSOR SIMON LAWRENCE CROFT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 25 January 2017 Professor of Parasitology from the Faculty of Infectious and Tropical Diseases, London School of Hygiene and Tropical Medicine, Professor Simon Lawrence Croft gave a Public Lecture on Research and Development entitled "Neglected Tropical Diseases Through Partnership" here today.